Analisis Pengaruh Pertumbuhan Penduduk, Tenaga Kerja, Investasi, dan Inflasi terhadap Pertumbuhan Ekonomi Kabupaten/Kota di Provinsi Jawa Tengah Tahun 2015-2019 - Mochammad Adrian Martadinata (Diponegoro Journal of Economics, 2022)
Economic growth is having a role in reflecting the success of the development of a region, economic growth itself is the increase in goods produced by economic actors at a certain time where this behavior is carried out to carry out economic activities. This economic activity which later makes a profit so that it becomes the capital to carry out other activities such as development which includes starting from social, economic and cultural issues as a whole. Economic growth is also a reflection that government policies are running properly and should be the targets that must be achieved in a certain period which is usually five years. The purpose of this study is to analyze the effect of population growth rate, labor, investment value and inflation rate on economic growth in Central Java Province city or district. The analytical tool used is OLS from 2015 to 2019. The results of the study explained that the variables that affect economic growth in Central Java Province city or district have different effects where the number of population growth has a positive and significant effect, labor has a positive and insignificant effect, investment has a positive and insignificant effect, and inflation has a negative and negative effect. not significant.